Basis set limit computation of dynamic polarizability at near‐resonance region. Issue 3 (11th May 2012) - Kato, Tetsuya; Yokoi, Yukina; Sekino, Hideo; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract We evaluate dynamic molecular polarizability at near‐resonance region using multiresolution multiwavelet (MRMW) basis set. The results obtained by traditional Gaussian basis sets are compared against the MRMW one. For perpendicular component, d‐aug functions seem to be necessary. Very large Gaussian basis sets beyond d‐aug‐cc‐pvqz can provide the results close to the complete space value obtained by the MRMW even for near‐resonance region. Improvement by enlargement of Gaussian functions is less systematic in the parallel component than in the perpendicular component. The competitiveness of the MRMW method against Gaussian methods in the computational efficiency for property evaluation is also discussed. © 2012 Wiley Periodicals, Inc.